Produktivitas Kerja Karyawan Berdasarkan Upah dan Lingkungan Kerja - Luh Ayu Yustika Dewi; I Nyoman Sujana (Ekuitas: Jurnal Pendidikan Ekonomi, 2021)
This study aims to examine the effect of (1) wage on the work productivity of employees at UD. PB Sari Muda, (2) the work environment on the work productivity of employees at UD. PB Sari Muda, (3) wage and work environment toward work productivity of employees at UD. PB Sari Muda. This type of research which was used in this research was causal research. The subjects of this research were all employees who work at UD. PB Sari Muda. The object of this research focused on wage, work environment and employee work productivity. The data were collected using interview techniques, questionnaires, observation and documentation which were analyzed by multiple linear regression analysis. The research result show that: (1) Partially, wage variable (X1) had a positive and significant effect on employee work productivity (Y) at UD. PB Sari Muda at 16.3%, (2) Partially, work environment variable (X2) had a positive and significant effect on employee work productivity (Y) at UD. PB Sari Muda of 83.6% and (3) The effect of wages (X1) and work environment (X2) serempakeously had a positive and significant effect on employee work productivity (Y) at UD. PB Sari Muda is 97.5% and the remaining 2.5% is influenced by other variables.